Devenir mère, Devenir sujet ? Parcours de femmes enceintes sans-papiers en France - Louise Virole-Zajde (Genre, Sexualité et Société)
This article analyses the process of becoming a mother when you are undocumented in France. It shows that pregnancy can be a source of subjectivation for these women. When they enter health and social care they are recognized as subjects. However, this process of political recognition depends on their pregnancy statute. Undocumented women in France are confined in a naturalized and racialized vision of maternity. Aware of this phenomenon, several women use their pregnant body as an ultimate resource to be recognized as a subject. Resistance of subjects suffers from an increasing power which stresses sex, race and class inequalities. Results are based on a qualitative study based on ethnographic observations (maternities, PMI, associations, health network) and on interviews with perinatal professionals and undocumented pregnant – or just given birth – women in Ile-de-France.